Synthesis of 4'-Hydroxychalcones, 1,ω-bis-(chalcon-4´-oxy)-alkanes Their Antibacterial Activity - Padwad, Manisha; Ingle, V.N. (Asian Journal of Chemistry, 2010)
1,ω-bis-(chalcon-4´-oxy)-alkanes have been synthesised by refluxing a mixture of 4´-hydroxychalcones, dihaloalkane, anhydrous K2CO3 and dry acetone. The structures were confirmed by chemical and spectral analyses and tested for antibacterial activity against S. aureus and E. coli.